The Effects of Advanced Plyometric Training Using WIMU-Pro Technology on Speed and Angular Acceleration and its Influence on Heart Rate Under varying Atmospheric Pressure and Magnetic Field Conditions in Young Fencers - Humam Sady Ibrahim (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
Sports is a field where training methods and techniques to improve physical performance such as fencing. This study presents a training program that can be implemented in sports clubs, specifically Baghdad Fencing Club. The study highlights the influence of environmental factors such as air pressure and magnetic fields on sports performance, which can help design training programs that take these variables into account. It emphasizes the importance of using modern technologies such as WIMU Pro in sports performance analysis. Despite significant advances in sports training methods, there is a lack of research focusing on the effects of advanced plyometric training on young fencing athletes, especially in relation to the use of modern technologies such as WIMU Pro. In addition, the influence of environmental factors such as air pressure and magnetic fields on physiological and motor performance has not been adequately discussed in scientific studies. It is evident that young fencing athletes struggle to achieve optimal performance due to the lack of training programs that integrate modern technology while taking into account environmental variables. Therefore, this study aims to address this gap by investigating the effects of advanced plyometric training using WIMU Pro technology on speed, acceleration, angle, heart rate and e in young fencing athletes. The purpose of this study is to develop a training program that utilizes advanced plyometric exercises using WIMU Pro technology; to determine the effects of advanced plyometric exercises on speed and acceleration in young fencing athletes at the Baghdad Fencing Club; to measure the effect of this exercise on the accuracy of the angle of movement during execution; to investigate the effects of training programs on heart rate under various conditions of air pressure and magnetic fields, and to provide practical recommendations for the development of training programs for young fencing athletes based on research findings. The study adopted an experimental design with both experimental and control groups, involving a sample of 24 fencing athletes. The results showed statistically significant increases in speed (8.16%), acceleration (16.13%), angle of motion (4.38%) and heart rate (6.67%) for the experimental group compared to the control group. The results also showed a slight effect of air pressure on heart rate, while magnetic fields had no obvious effect.